Investigation of Electrochemical Parameters on Cost-Effective Zn/Ni-Based Electrocatalysts for Electrochemical CO2Reduction Reaction to SYNGAS(H2+CO) - Shahrestani, S. (IOP Publishing Ltd, 2022)
Electrochemical CO2 reduction reaction (CO2RR) has been studied in 0.1 M of KCl (pH of 6.96), NaHCO3 (pH of 8.3) and K2CO3 (pH of 11.36) cathodic solutions with various counter electrodes including graphite rod, SS316 rod and Pt mesh at different potential ranges on the Znx-Ni1-x bimetallic electrocatalysts. Among the Znx-Ni1-x electrocatalysts, the Zn-Ni electrode with a composition of 65 wt Zn and 35 wt Ni and cluster-like microstructure has the best performance for CO2RR by according to minimum coke formation and optimum CO and H2 faradaic efficiencies (CO FE = 55 and H2 FE = 45). The cyclic voltammetry (CV) measurements and gas chromatography (GC) analysis for the CO2RR showed that KCl solution as the cathodic electrolyte with pH of 7 has the best performance and appropriate faradaic efficiency for H2 (40) and CO(30) products in low potential value (-0.6 v) in this study. The best potential range for the CO2RR on the Zn-Ni bimetallic electrocatalyst in KCl solution with the scan rate (SR) 0.05 V. s-1 is between -0.3 V to -1 V vs Ag/AgCl. The use of stainless-steel electrode (SS316) as a counter electrode for electrochemical CO2RR is cost-effective and performs better than graphite electrode, but at high applied potential it oxidizes and dissolves in the electrolyte and then ions transfer to the Nafion membrane and poisons it. Â© 2022 The Electrochemical Society ("ECS"). Published on behalf of ECS by IOP Publishing Limited. DOI: 10.1149/1945-7111/ac645a.